Geochemical implications for gas hydrate occurrence and seepage at Sites GMGS5-W07 and W09 in Qiongdongnan Basin, South China Sea - Lu, Yinghan; Yang, Hailin; Lu, Hailong; Fang, Yunxin; Kuang, Zenggui (Frontiers in Earth Science, 2022)
The compositions and morphological characteristics of minerals and the cycle of trace elements in sedimentary environment are considered to be powerful indicators for the occurrence and evolution of gas hydrates. In this paper, total organic carbon (TOC) content, particle size distribution, mineral composition, element distribution, and iron speciation of sediments from Sites GMGS5-W07 and GMGS5-W09 of South China Sea are studied. The high content of TOC and the occurrence of authigenic carbonate, sulfate minerals, and pyrite suggest the accumulation potential of gas hydrate at the two sites. In the hydrate-bearing layers, redox-sensitive trace elements such as Co, Ni, Cu, Zn, As, Sb, Fe, and Mn are enriched, while reducing and acidic conditions lead to the accumulation of Fe and the increase of Fe(Ⅱ) species proportion in sediments. The dominant factors of the element behavior at the two sites are distinguished by the Pearson correlation analysis between trace elements and TOC, and the results show that the circulation of trace elements at Site W07 is more strongly affected by methane-rich fluids than at Site W09. Therefore, more intense methane seepage might have happened at Site W07, and this conjecture has been further confirmed by higher aragonite content in sediments as reflected by the Sr/Ca-Mg/Ca model. Based on these results, the change in seepage intensity is not associated with the occurrence of gas hydrate.